Faster deterministic algorithms for Co-path Packing and Co-path/cycle Packing - Tsur, Dekel (Journal of combinatorial optimization, 2022)
In the Co-path Packing (resp., Co-path/cycle Packing ) problem, the input is a graph G and an integer k , and the goal is to decide whether there is a set of at most k vertices whose removal from G results in a graph which is a collection of induced paths (resp., induced paths and cycles). In this paper we give deterministic O ∗ ( 3 k ) -time algorithms for Co-path Packing and Co-path/cycle Packing .